Experimental and numerical analysis of CFRP-concrete joint bond behavior after exposure to wet-dry cycles. (1st January 2023) - Al-Lami, Karrar; Colombi, Pierluigi; D'Antino, Tommaso
Abstract: Fiber-reinforced polymer (FRP) composites have been largely used for strengthening and retrofitting reinforced concrete members in the last few decades. However, limited information is available regarding their performance after prolonged exposure to different environmental conditions. In this paper, the effect of wet-dry cycles on the bond behavior of carbon FRP-concrete joints tested using a single-lap direct shear test set-up is investigated. Specimens were exposed to 50 wet-dry cycles, each comprised of 6 h of immersion in water at 25 °C followed by 18 h of drying at 50 °C. The digital image correlation technique was used to obtain the displacement field of the composite and determine the cohesive material law and fracture energy of the FRP-concrete interface. A finite element model was then used to reproduce the load response and reinforcement strain profile observed experimentally. The results show that wet-dry cycles affect the FRP-concrete bond properties and change the failure mode from a cohesive debonding within the concrete substrate to an adhesive debonding within the interface.